Oesophageal eosinophilia accompanies food allergy to hen egg white protein in young pigs. Issue 1 (26th November 2019) - Plundrich, Nathalie J.; Smith, Andrew R.; Borst, Luke B.; Snider, Douglas B.; Käser, Tobias; Dellon, Evan S.; Blikslager, Anthony T.; Odle, Jack; Lila, Mary Ann; Laster, Scott M.
Abstract: Background: Esophagitis with eosinophilia, inflammation, and fibrosis represent a chronic condition in humans with food allergies. Objective: In this investigation, we asked whether esophagitis with an eosinophilic component is observed in young pigs rendered allergic to hen egg white protein (HEWP). Methods: Food allergy was induced in young pigs using two protocols. In one protocol, sensitized pigs were challenged by gavage with a single dose of HEWP. Clinical signs were monitored for 24 hours, and then, gastrointestinal (GI) tissues were collected for histological examination. The phenotype of circulating, ovalbumin (OVA)‐specific T cells also was examined in HEWP challenged animals. In the second protocol, sensitized animals were fed HEWP for 28 days. Animals were then examined by endoscopy and gastrointestinal tissues collected for histological examination. Results: In pigs challenged by gavage with HEWP, clinical signs were noted in 5/6 pigs including diarrhoea, emesis, and skin rash. Clinical signs were not seen in any control group. Histological analysis revealed significant levels of oesophageal eosinophilic infiltration ( P < .05) in 4/6 of these animals, with two also displaying eosinophilic infiltration in the stomach. Eosinophils were not increased in ileum or colon samples. Increased numbers of circulating, OVA‐specific CD4 + T cells also were observed in pigs that received HEWP by gavage. In the group of animals fed HEWP, endoscopy revealed clinical signs of esophagitis including oedema, granularity, white spots, and furrowing, while histology revealed oedema, immune cell infiltration, and basal zone hyperplasia. Conclusions and Clinical Relevance: Food allergy in the pig can be associated with esophagitis based on histological and endoscopic findings, including eosinophilic infiltration. The young pig may, therefore, be a useful large animal model for the study of eosinophilic esophagitis in humans.